Influence of Welding on Dynamic Fracture Toughness of Strenx 700MC Steel - Schmidová, Eva; Bozkurt, Fatih; Culek, Bohumil; M R, Sunilkumar; Kucharikova, Lenka; Uhricik, Milan (MDPI AG (Multidisciplinary Digital Publishing Institute), 2019)
Thermomechanically processed high-strength steels feature specific fracture behavior. One of the decisive criteria for their application is their stability against internal defects during impact loads, especially in connection with the welding. The work is focused on experimental analyses of the influence of welding on static and dynamic fracture toughness of Strenx 700MC steel. The fracture toughness was determined using the circumferentially notched round bar specimens during static loads and two dynamic load levels. To achieve a homogeneous zone for the requirements of fracture toughness tests, simulation of the welding influence was performed. Fractographic and metallographic analyses described a specific fracture behavior controlled by the internal structural heterogeneity. A limiting degradation process due to welding was identified by the microstructural analysis.
Vliv svařování na dynamickou lomovou houževnatost oceli Strenx 700MC
Keywords: dynamic fracture toughness; high strength steels; fracture behavior; welding influence; heat-affected zone; simulation of welding; heterogeneous carbide precipitation; dynamická lomová houževnatost; vysokopevné oceli; lomové chování; vliv svařování; heterogenní precipitace karbidů